ANALISIS DAMPAK KEABSAHAN PERJANJIAN FIDUSIA (STUDI KASUS: PERJANJIAN FIDUSIA ANTARA PT. X DENGAN BANK B) - Jefri Purnama (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
This research discusses about the object of fiduciary collateral agreement in the form of plastic raw material inventory that has been pledged to Bank A by Company X, then repayment occurs, the object of the agreement is not written-off (referred to as “roya”), but is to be used as a fiduciary guarantee again by Company X to Bank B. The issues raised in this research are about the impact of the validity of the credit agreement that has been paid off, while the fiduciary object has not been written off and has been used as a collateral with fiduciary ways to another creditor, including what form of legal protection available if the debtor defaults. This research is a normative legal research using primary data. In the result of the research, the authors concludes that the strength of the fiduciary engagement was born from the accessoire agreement, so that if the credit agreement as the principal agreement terminates, then the basis of the fiduciary engagement will also end. So if the debtor binds the object as a fiduciary collateral to another creditor, the object is considered legitimate to be used as collateral. The legal protection of the creditors in the form of executorial power of fiduciary certificate which holds the same levy as a court ruling that has final legal force. Legal action can be taken to carry out the execution with the execution by the court through parate executie auction or voluntary sales of collateral between creditor and debtor.